LITERATURE REVIEW: ACCOUNTABILITY AND THE CONCEPT OF VALUE FOR MONEY IN REGIONAL FINANCIAL MANAGEMENT IN INDONESIA - Adhinda Cahyani Putri; Nuraini Novitasari; Kurnia Putri Sugiarti; Himatul Khasanah (Universitas Cenderawasih, 2024)
Abstract This research aims to provide reflections regarding accountability and the concept of value for money in regional financial management in Indonesia. The method used in this research is charting the field. Samples were taken from 55 accredited journals in Indonesia and 59 articles were obtained during 2018-2023. The results of this research show that the actual implementation of accountability and the concept of value for money in regional financial management has been partially maximized. The novelty of this research is examining accountability and the concept of value for money in regional financial management in Indonesia using the charting the field method. Keywords: Accountability, Value for Money, Regional Financial Management, Public Sector, Accounting Research